Bulleit proof : how I took a 150-year-old family recipe and a revolver, and disrupted the entire liquor industry one bottle, one sip, one handshake at a time - Bulleit, Tom, 1942-; Eisenstock, Alan (John Wiley & Sons, Inc., 2020)
"About a year ago, Tom Bulleit stood on a stage inside a tent the size of a big-top on the occasion of--in order of importance--his thirtieth wedding anniversary, the dedication of the new Bulleit Distillery in Shelbyville, Kentucky, and his seventy-fourth birthday. At one point, overcome by a sudden and surprising wave of emotion, he gripped the podium, looked into the blur of faces before him, and said, "I don't believe our lives are told in years... or months... or weeks. I believe we live our lives in moments." That's what this book will be--a life told in moments--moments of joy, triumph, love, loss, discovery, commitment, faith, fortitude, struggle, persistence, and success; at least his definition of success, which has little to do with money. At its core, the book will weave through it a thread of survival--in war, in business, in life. Tom nearly died twice, once in a foxhole and once in an oncology ward, and, for the record, he never met an atheist in either place. He'll reveal all, no holds barred, no punches pulled"--